Molecular Characterization of Staphylococcus aureus Isolated from Bovine Mastitis and Close Human Contacts in South African Dairy Herds: Genetic Diversity and Inter-Species Host Transmission - Schmidt, Tracy; Kock, Marleen M.; Ehlers, Marthie M. (Frontiers in Microbiology, 2017)
Staphylococcus aureus is one of the most common etiological agents of contagious bovine mastitis worldwide. The purpose of this study was to genetically characterize a collection of S. aureus isolates (bovine = 146, human = 12) recovered from cases of bovine mastitis and nasal swabs of close human contacts in the dairy environment. Isolates were screened for a combination of clinically significant antimicrobial and virulence gene markers whilst the molecular epidemiology of these isolates and possible inter-species host transmission was investigated using a combination of genotyping techniques. None of the isolates under evaluation tested positive for methicillin or vancomycin resistance encoding genes. Twenty seven percent of the bovine S. aureus isolates tested positive for one or more of the pyrogenic toxin superantigen (PTSAg) genes with the sec and sell genes predominating. Comparatively, 83% of the human S. aureus isolates tested positive for one or more PTSAg genes with a greater variety of genes being detected. Genomic DNA macrorestriction followed by pulsed-field gel electrophoresis (PFGE) of the bovine isolates generated 58 electrophoretic patterns which grouped into 10 pulsotypes at an 80% similarity level. The majority of the bovine isolates, 93.2% (136/146), clustered into four major pulsotypes. Seven sequence types (ST) were identified among the representative bovine S. aureus isolates genotyped, including: ST8 (CC8), ST97 (CC97), ST351 (CC705), ST352 (CC97), ST508 (CC45), ST2992 (CC97) and a novel sequence type, ST3538 (CC97). Based on PFGE analysis, greater genetic diversity was observed among the human S. aureus isolates. Bovine and human isolates from three sampling sites clustered together and were genotypically indistinguishable. Two of the isolates, ST97 and ST352 belong to the common bovine lineage CC97, and their isolation from close human contacts suggests zoonotic transfer. In the context of this study, the third isolate, ST8 (CC8), is believed to be a human clone which has transferred to a dairy cow and has subsequently caused mastitis. The detection of indistinguishable S. aureus isolates from bovine and human hosts at three of the sampling sites is suggestive of bacterial transmission and supports the need for vigilant monitoring of staphylococcal populations at the human-animal interface.